Mineral Depletion, with Special Reference to Petroleum - Adelman, M. A. (The Review of Economics and Statistics, 1990)
Two implications of received theory are (1) mineral net prices rise at the riskless interest rate, and (2) in-ground value is equal to the current net price. Both propositions are false. A correct theory has been joined to mistaken premises. Mineral resources are inexhaustible. The economic problem is not the intertemporal allocation of a stock but coping with the cost of a flow of reserve accretions. Mineral scarcity and price are the uncertain fluctuating result of a tug-of-war between diminishing returns versus increasing knowledge. Hence minerals are risky assets. Development cost, finding cost, and user cost (the penalty for development/production today instead of tomorrow) are all substitutes. Hence change in any one is a proxy for change in any other. Development cost is observable, and has been stable in many countries for pro- longed periods. User cost was also stable in the USA. There is no sign of any pattern of gradual depletion and rising cost. A simple model of an individual reservoir explains observed relations of value and price. The rate of interest has both a positive and negative effect upon the rate of reservoir depletion. The net effect of a change is therefore weak. Expropriation of low-cost oil fields, had they been operated independently to maximize value, would have led to drastic increases in depletion rates. The fact of decrease proves collusive restriction of output to maintain prices.